PENERAPAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) BERBANTUAN MEDIA PETA KONSEP TERHADAP HASIL BELAJAR MATERI HIDROLISIS GARAM PADA SISWA KELAS XI IPA MAN 1 BANJARMASIN - Noorma Andini (Universitas Lambung Mangkurat, 2015)
Abstract. This study concerning the effect of the use of the model-assisted learning Team Assisted Individualization media concept map. This study aims (1) to determine differences in cognitive achievement between students who use learning model Team Assisted Individualization media aided concept maps with students using the learning model without assisted Team Assisted Individualization media concept map on the material hydrolysis of salt (2) determine students' response to learning model using Team Assisted Individualization media aided concept maps. This research method is a quasi-experiment. Samples were students of class XI-Sains 1 and XI-Sains 2 in MAN 1 Banjarmasin numbered 74 people. The research design used was the nonequivalent control group design. Collecting data using achievement test and questionnaire responses. The data were analyzed using t-test with a significance level of 5%. Techniques used for the analysis of the percentage of responses. Calculation of the t-test showed that tcount> ttable therefore concluded that there are significant differences in learning outcomes between experimental and control classes. As for the response of the students as much as 75.08% gave a positive response in the experimental.keywords: model team assisted individualization of learning, concept maps, learning outcomes, hydrolysis of salt.